2003
DOI: 10.5688/aj6704108
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Service Quality Dimensions of Pharmaceutical Education

Abstract: Objectives. Describe the perceptual dimensions of student assessments of the quality of their education. Link those dimensions with student satisfaction with their educational experience. Methods. A 37-item educational service quality instrument and a seven-item satisfaction scale were administered to 372 students in their final year of education in years 1999 to 2002. Results. Factor analysis identified 5 dimensions of service quality labeled resources, interpersonal behavior of faculty, faculty expertise, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 8 publications
1
33
0
4
Order By: Relevance
“…Oliver (1997) defined customers' satisfaction as the feedback regarding the fulfillment of the customers' requirements. Holford and Patkar (2003) in Handoyos (2006) stated that there are five items of overall students' satisfaction comprising the quality of the facilities, quality of the learning process, quality of the service, quality of the curriculum, and quality of the instructional implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Oliver (1997) defined customers' satisfaction as the feedback regarding the fulfillment of the customers' requirements. Holford and Patkar (2003) in Handoyos (2006) stated that there are five items of overall students' satisfaction comprising the quality of the facilities, quality of the learning process, quality of the service, quality of the curriculum, and quality of the instructional implementation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The satisfaction survey tool was developed by adapting questions from existing instruments to assess student-reported satisfaction with the combination of student-directed learning techniques and tools used in both courses. 8,9 The confidence and satisfaction survey tools are 18 and 28 item, 5-point Likert scales ranging from 1 5 strongly disagree to 5 5 strongly agree.…”
Section: Evaluation and Assessmentmentioning
confidence: 99%
“…16 In the recent past, in the context of India, Gupta and Mandal (2016) have conceptualized with the help of the literature review and identified five dimensions and these are Infrastructure, Academic and Social Reputation, Career Development, Academic Program and Administrative system. This research left immense scope for future improvement.…”
Section: Univqualmentioning
confidence: 99%
“…The researches which have been carried out in an outside Indian environment [14][15][16] are empirical in nature, but at the same time unwise to extend without modification into the Indian situation since service quality expectation is not neutral to culture. 12,13,38 The research that has been executed in India by Gupta and Mandal (2016) 17 is a kind of conceptual analysis for the measurement of service quality determinants and judgmental findings of Gupta and Mandal (2016) 17 opined that five number of factors can measure the service quality.…”
Section: Research Query (Rq) Developmentmentioning
confidence: 99%
See 1 more Smart Citation